Determinación del costo de producción del yogurt en la Quinta Experimental Punzara de la Universidad Nacional de Loja, periodo del 01 de octubre al 31 de diciembre del 2023. - Yaguana Valarezo, Adriana Yamile (2024)
The Curricular Integration Project entitled: DETERMINATION OF YOGHURT PRODUCTION COSTS AT THE PUNZARA EXPERIMENTAL FACTORY OF THE UNIVERSIDAD NACIONAL DE LOJA, PERIOD OCTOBER 01st TO DECEMBER 31st 2023, was carried out to provide an information tool and useful technical procedures to improve the determination of the cost of production of dairy products such as yogurt; its application offers control of the three cost elements of raw materials, human labor, and indirect production costs, enabling the farm manager to know the individual and total production costs at the end of each batch as a reference for establishing the selling price of the product while maintaining updated inventories of raw materials and finished products. The research project was developed over three months during the yogurt production process, fulfilling the proposed objectives; first, a flow chart of the yogurt production process was designed including procedures and policies; for the second objective, basic formats and records were developed and applied for the control of raw materials, labor, and indirect production costs; production orders, requisitions, kardex cards, clock cards, time cards, payment cards, and cost sheets were elaborated; Finally, for the third objective, an initial inventory was created, and a specific plan and manual of accounts were prepared by the factory's activities, which allowed the recording in the journal, general ledger, and trial balance, which provided information on the costs generated in each production for the preparation of the statement of the expenses of products sold. It is concluded that, with the development of this curricular integration work, it was possible to establish with certainty the individual and total production costs of yogurt for October, November, and December 2023. Therefore, it is recommended to use this cost-determination process for future activities to know the cost of yogurt production at the Punzara Experimental Farm.